Intelligent Information System of Heterogeneous Medical Data Analysis - Єрохін, А. Л.; Турута, О. П.; Нечипоренко, А. С.; Бабій, А. С. (My University, 2017)
This paper describes the intelligent information system of heterogeneous medical data analysis for Ear Nose Throat (ENT) domain. Machine learning (ML) methods for medical data processing are analyzed. The scenario of machine learning algorithms for data processing in intelligent information system was developed. Supervised learning algorithms for classification task were implemented, their efficiency was validated. The proposed approach allows to improve the decision-making process and provide pre-surgical and post-surgical assessment of patients.
Keywords: Heterogeneous data; Intelligent information system; Machine learning; Feature extraction; Classification